A self-triggering system for a cold-cathode thyratron in a pulse voltage generator - Egorov I. S. Ivan Sergeevich; Esipov V. S. Viktor Sergeevich; Lukonin E. I. Evgeny Ivanovich; Poloskov A. V. Artem Viktorovich (Electronics And Radio Engineering, 2015)
Title screen